Mengamati Aspek-Aspek Visual Pertunjukan Tari Sebagai Pengayaan Kajian Senirupa - Anis Sujana (Journal of Visual Art and Design, 2007)
According to the medium, arts can be classified into the art of visual, the art of hearing, and the art of words. Those included in the art of visual are dance and fine art, in the art of hearing is music and in the art of words is poetry. This paper describes one of the art of the visual"”dance, which use human body and its movement as a medium of expression. Fact shows that a dance performance exists due to the involvement of supporting elements such as visual disposition. Certain dances limit themselves to the supporting elements of costumes, make-up, property (tools) and musical instruments; others equip with stages, decorations, and lightings. Traditional dances"”in particular"”extensively equip themselves with supporting elements to show its characteristics. Thus, since dance requires the supporting element of visuals, it is reasonable to observe it as similar to the way we observe the object of fine art. The scope of observation for the supporting elements of dance performance may cover the whole visual events or just merely one of the scenes. Therefore, a contextual knowledge of both inside and outside can be fully grasped to form the background of the dance performance.